2022
DOI: 10.1021/acs.jproteome.2c00047
|View full text |Cite
|
Sign up to set email alerts
|

Well-Plate μFASP for Proteomic Analysis of Single Pancreatic Islets

Abstract: Filter-aided sample preparation (FASP) is widely used in bottom-up proteomics for tryptic digestion. However, the sample recovery yield of this method is limited by the amount of the starting material. While ∼100 ng of digested protein is sufficient for thorough protein identification, proteomic information gets lost with a protein content <10 μg due to incomplete peptide recovery from the filter. We developed and optimized a flexible well-plate μFASP device and protocol that is suitable for an ∼1 μg protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Peptic peptides were sequenced with PLGS 3.0.3 (Waters Corporation, Manchester, United Kingdom), as previously described, , with a modification of setting enzymes to “non-specific.” CE–MS data obtained with UDMS E were searched against a database of UNIPROT peptide sequence entries for HBA_BOVIN, HBB_BOVIN, and PEPA_PIG. Complete data were further processed with the HX-DEAL module in Mass Spec Studio for HDX-analysis …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peptic peptides were sequenced with PLGS 3.0.3 (Waters Corporation, Manchester, United Kingdom), as previously described, , with a modification of setting enzymes to “non-specific.” CE–MS data obtained with UDMS E were searched against a database of UNIPROT peptide sequence entries for HBA_BOVIN, HBB_BOVIN, and PEPA_PIG. Complete data were further processed with the HX-DEAL module in Mass Spec Studio for HDX-analysis …”
Section: Methodsmentioning
confidence: 99%
“…Unlabeled peptides were analyzed in data independent acquisition (DIA) mode using the UDMS E method with instrument settings previously reported for this instrument, unless otherwise stated. 36 , 37 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have also developed a 96-well plate version of the micro-FASP method, which showed high reproducibility (R 2 > 0.99) when processing Xenopus laevis lysate (12 replicates, 1 μg each). Similarly, Sandbaumhüter et al developed a flexible well-plate μFASP device suitable for a small amount of protein (1 μg) [ 113 ]. The filter area for the centrifugal filter units of the conventional FASP was reduced from approximately 119 mm 2 to 0.785 mm 2 for the μFASP device.…”
Section: From Proteins To Peptidesmentioning
confidence: 99%